Kandungan Gizi, Beta Karoten dan Antioksidan pada Tepung Pisang Tongka Langit (Musa troglodytarum L.) - Ika Yohanna Pratiwi; Oki Krisbianto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Banana fruit cultivar Tongka Langit is a typical plant from Moluccas which has not widely used and observed just yet. It has been believed and used by locals to relieve body heat, clean the kidneys, and keep the health of the digestion tract, but without scientific proof. This study aims the nutrition content of Tongka Langit flour, along with its carotenoids, beta carotene, and antioxidant content. The banana fruit was dried at 60 oC for 2 hours. Banana flour had been analyzed for moisture content, levels of ashes, levels of protein, the fibers, carbohydrates, vitamin C, mineral, carotenoids and antioxidant. It had been found that Tongka Langit flour contained 331,03 calories, 4,66% protein, 83,72% carbohydrate and 16,59% dietary fibers. Tongka Langit flour contained 7,92 mg/ 100 mg carotenoid total which 18,56% was beta carotene. As much as 0.35 mg/kg flavonoid was also found, along with its high level of antioxidant activity.